2020
DOI: 10.1177/2309499019896882
|View full text |Cite
|
Sign up to set email alerts
|

The impact of plating level on the postoperative loss of cervical lordosis in alternative skipped-level plating laminoplasty

Abstract: Purpose: The aim of this study is to evaluate the impact of plating level on the loss of cervical lordosis (LCL) after laminoplasty with skipped-level plating. Methods: This retrospective study included patients who underwent alternative skipped-level plating laminoplasty from C3 to C6. Patients were divided into two groups according to the plating level. Group 1 had miniplate fixed at C3 and C5 (C3/C5 group), while patients in group 2 were fixed at C4 and C6 (C4/C6 group). The outcome of interest was the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…One study compared laminoplasty starting at either C3 or C4 and reported significantly less loss of lordosis in the C4 group [34]. When using skip-level plating, another group reported improved postoperative lordosis when plating at C4 and C6 rather than C3 and C5 [35]. Finally, another group reported good clinical outcomes using partial undercutting ("dome") laminectomy at C3 above C4 laminoplasty instead of C3 laminoplasty, but their study did not include a comparison group [36].…”
Section: Introductionmentioning
confidence: 99%
“…One study compared laminoplasty starting at either C3 or C4 and reported significantly less loss of lordosis in the C4 group [34]. When using skip-level plating, another group reported improved postoperative lordosis when plating at C4 and C6 rather than C3 and C5 [35]. Finally, another group reported good clinical outcomes using partial undercutting ("dome") laminectomy at C3 above C4 laminoplasty instead of C3 laminoplasty, but their study did not include a comparison group [36].…”
Section: Introductionmentioning
confidence: 99%